Answer:
g(1) = 0
=
lgn= ) +m
g(n) = g(n - 1) +n
=
-
n
g(2) =12
Step-by-step explanation:
12345678910
Answer: 19 + 3x
Step-by-step explanation:
Given : 4 + 3(5+x)
expanding , we have
4 + 15 + 3x
= 19 + 3x
Therefore :
4 + 3 ( 5 + x ) = 19 + 3x
I believe the answer is C
Answer:
<u><em>67</em></u>
Step-by-step explanation:
<u><em>50-40+87-30</em></u>
=50+(- 40)+87(-30)
=50+87+(-40)+(-30)
=(50+87+(-40)+(-30)
=137+(-70)
=67
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em>when he wins, we add points. When he loses ,we subtract points.The score is 50 points. We right an expression to find the final score </em></u>